2018
DOI: 10.1155/2018/6502890
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Assessment of Incorporating Copper Slag as a Sand Substitute to Attain Sustainable Production Perspective in Concrete

Abstract: Motivated by the sustainable production perspective, a laboratory testing program is exercised to ascertain the feasibility of utilizing copper slag in place of the natural fine aggregate in concrete. Totally, fifteen concrete mixtures were prepared to incorporate copper slag in place of the fine aggregate in concrete. e attributes of concrete specimens made with varying proportions of copper slag were compared (ranging from 0% to 100% substitution) at a w/c ratio of 0.44, and the optimum percentage of copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…The compressive strength of the concrete generally showed increase up to the 50% substitution of copper slag but reduced significantly due to increase in the free water demand remained in the mix in excess to the required for the hydration of cement paste as shown in the Figure 6. 47,50 Figure 6.Relationship between slump and strength of HPC 47 Some researchers have also shown that Compressive strengths after 7, 28, 90 days of curing periods showed the downfall as the percentage of copper slag increased 40 contradicting previous studies of. 47,50 Concrete blends with 60% of copper slag resulted in the compressive strength equivalent to the strength of the controlled mix with hundred percent of fine aggregates.…”
Section: Mechanical Properties Compressive Strengthmentioning
confidence: 94%
See 3 more Smart Citations
“…The compressive strength of the concrete generally showed increase up to the 50% substitution of copper slag but reduced significantly due to increase in the free water demand remained in the mix in excess to the required for the hydration of cement paste as shown in the Figure 6. 47,50 Figure 6.Relationship between slump and strength of HPC 47 Some researchers have also shown that Compressive strengths after 7, 28, 90 days of curing periods showed the downfall as the percentage of copper slag increased 40 contradicting previous studies of. 47,50 Concrete blends with 60% of copper slag resulted in the compressive strength equivalent to the strength of the controlled mix with hundred percent of fine aggregates.…”
Section: Mechanical Properties Compressive Strengthmentioning
confidence: 94%
“…47,50 Figure 6.Relationship between slump and strength of HPC 47 Some researchers have also shown that Compressive strengths after 7, 28, 90 days of curing periods showed the downfall as the percentage of copper slag increased 40 contradicting previous studies of. 47,50 Concrete blends with 60% of copper slag resulted in the compressive strength equivalent to the strength of the controlled mix with hundred percent of fine aggregates. 45 A rapid decline in compressive strength was noted down with 80%-100% copper slag substitution as compared to controlled blend.…”
Section: Mechanical Properties Compressive Strengthmentioning
confidence: 94%
See 2 more Smart Citations
“…Keeping the above facts in mind, the research team focused on using slag and fly ash for the substitution of ordinary sand. Both of the waste materials are commonly available in industrialized countries and are partially used for cement production [23] and for the creation of ordinary concrete [24,25].…”
Section: Introductionmentioning
confidence: 99%